The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/676740
|View full text |Cite
|
Sign up to set email alerts
|

Role of Optical Coherence Tomography on Corneal Surface Laser Ablation

Abstract: This paper focuses on reviewing the roles of optical coherence tomography (OCT) on corneal surface laser ablation procedures. OCT is an optical imaging modality that uses low-coherence interferometry to provide noninvasive cross-sectional imaging of tissue microstructure in vivo. There are two types of OCTs, each with transverse and axial spatial resolutions of a few micrometers: the time-domain and the fourier-domain OCTs. Both have been increasingly used by refractive surgeons and have specific advantages. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
(105 reference statements)
0
9
0
1
Order By: Relevance
“…11 Previous studies on agreement between USP and OCT measurements of central corneal thickness have reported thinner readings obtained by OCT compared with USP. USP relies on accurate perpendicular placement of the probe on the cornea to yield reliable measurements, which is based on the examiner's subjective judgment, whereas for OCT imaging, the corneal apical reflection will be an objective indication to ensure correct scanning position.…”
Section: Discussionmentioning
confidence: 94%
“…11 Previous studies on agreement between USP and OCT measurements of central corneal thickness have reported thinner readings obtained by OCT compared with USP. USP relies on accurate perpendicular placement of the probe on the cornea to yield reliable measurements, which is based on the examiner's subjective judgment, whereas for OCT imaging, the corneal apical reflection will be an objective indication to ensure correct scanning position.…”
Section: Discussionmentioning
confidence: 94%
“…After further improvements and testing, this miniature forward-imaging OCT probe may have the potential for guiding laser surgery. Previous studies have shown that real-time OCT imaging of laser ablation is possible through an external imaging system and through large probes [1][2][3][4][5][6][7][8][9], but not with a 0.5 mm diameter handheld probe.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) has emerged as an important medical imaging tool to evaluate structures within the eye, skin, heart, larynx, and teeth amongst other biological tissues before and after surgical ablation [1][2][3][4][5][6][7][8][9]. Optical coherence tomography imaging of laser ablation has been previously achieved through an external imaging system and through large probes [1][2][3][4][5][6][7][8][9], but not through a miniature forward-imaging probe 0.5 mm in diameter. Moreover, most studies have used OCT to evaluate the tissue after completion of the laser ablation and not continuously during the actual lasing process.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of using lasers to produce these holes include the feasibility of incorporating real-time sensing and feedback mechanisms for high accuracy and precision, 3,30 which is critical to applications such as pedicle screw placement. There are several issues in using laser ablation on hard tissue, such as thermal damage to collateral tissue, shallow penetration depth and difficulty in producing large-diameter and deep holes, and time-consuming drilling time.…”
Section: Summary and Discussionmentioning
confidence: 99%